Climate change adaptation policy and planning for cultural heritage in low- and middle-income countries. (December 2022) - Daly, Cathy; Fatorić, Sandra; Carmichael, Bethune; Pittungnapoo, Witiya; Adetunji, Olufemi; Hollesen, Jørgen; Nakhaei, Masoud; Diaz, Alberto Herrera
Abstract: Abstract : Climate change threatens archaeological sites and cultural landscapes globally. While to date, awareness and action around cultural heritage and climate change adaptation planning has focused on Europe and North America, in this article, the authors address adaptation policy and measures for heritage sites in low- and middle-income countries. Using a review of national adaptation plans, expert survey and five case studies, results show the varied climate change adaptation responses across four continents, their strengths and weaknesses, and the barriers to be addressed to ensure better integration of cultural heritage in climate change adaptation planning.